Using Pictionary Game to Increase Learners’ Vocabulary Mastery in English Language Instruction - Hamer, Welliam; Lely, Ledy Nur (Journal of English Education Studies, 2019)
This article aims at sharing information on how pictionary game is used to increase the learners’ vacabulary mastery in the process of teaching and learning. It is clear that vocabulary is one of components of English language. When the learners are reading, they need to master vocabulary related to certain topic. Therefore vocabulary is important thing in learning English. However, mastering English vocabularies is not easy. English is foreign language in which learning English is often considered to be difficult to comprehend. This problem can be seen from the unsatisfactory result when learning English. The learning processs commonly used in the classroom just puts the teacher as a center of learning. It means that the teacher always dominates him/herself to teach, not to focus on how the learners learn effectively. This makes the learners passive and less interested in following the course of learning. In fact the learners’ interest is the most important factor in the study. Interest can be developed if the learning process run with fun, vary, and conducive athmosphere. There are many factors that can support the existance of an increase in the study, i.e. teachers, learners, materials, media, methods, and other learning sources. One factor that can help the learners learn vocabulary is the use of pictionary game. In this study, pictionary game is a classic game of drawing and guessing pictures. Pictionary game can also increase the imagination of learners, where learners are asked to draw according to the word given by the teachers. Things that are needed to play pictionary game are a list or card of vocabulary items, whiteboard, calkboard, or smart board and markers. Pictionary game will help learners to get involved in classroom activities. Other advantages of using pictionary game can be concluded that it provides fun language practice in the various language skills.